14-Year Retrospective Review of Audiology Graduate Admission Data: Comparative Analysis with Other First Professional Health Programs. - Needleman, Alyssa R.; Gaffney, Patricia A.; Friedland, Erica B.; Alamu, Josiah (Internet Journal of Allied Health Sciences & Practice, 2025)
Purpose: Demographic and cognitive data on students entering audiology programs is incomplete, and there is a lack of comparison among audiology students and those entering other first professional health (FPH) programs. This paper is the first of a multi-part series to provide evidence into the characteristics of the typical audiology student and their graduate outcomes. This is valuable for improving recruiting, admissions, retention, and success rates of audiology programs. A comprehensive descriptive analysis of admission criteria was performed for students who entered the NSU Doctor of Audiology (AuD) program over the last 14 years. Additionally, NSU admissions data was compared to other AuD and FPH programs in the United States. Methods: Demographic and quantitative data were abstracted retrospectively from the NSU AuD student data repository. Data from other health professions was obtained from their published common application system reports and/or the educational organization associated with each profession. Results: The NSU AuD program enrolled 281 students, the majority female and White, consistent with the majority of FPH students. All FPH programs skew female, except dental medicine. Approximately 69% of students entering the NSU AuD program come from pre-professional majors, compared with more than 60% of students in dental, optometry, and pharmacy with physical sciences majors. AuD programs nationally had higher undergraduate GPAs than all other FPH programs; GREs were consistent with other programs. Thousands more students apply to FPH programs than AuD, with an inverse relationship between number of applicants and number of academic programs, resulting in a disproportionately high acceptance rate among AuD programs. Conclusions: Characteristics of students entering the NSU AuD program, including demographic and cognitive metrics are comparable to other AuD programs nationally. While many admissions metrics are similar, there is a disparity in total number of applicants to AuD programs compared to other FPH programs, as well as a lower representation from physical sciences backgrounds.